2008
DOI: 10.1109/tgrs.2008.2005202
|View full text |Cite
|
Sign up to set email alerts
|

Constellation Deployment for the FORMOSAT-3/COSMIC Mission

Abstract: The FORMOSA Satellite Series No. 3/Constellation Observing System for Meteorology, Ionosphere and Climate (FORMOSAT-3/COSMIC) spacecraft constellation consisting of six low-earth-orbiting satellites is the world's first operational Global Positioning System (GPS) radio occultation mission. The mission has been jointly developed by the National Space Organization of Taiwan and the University Corporation for Atmospheric Research of the U.S. in collaboration with the Jet Propulsion Laboratory, NASA, and the Naval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…The primary scientific goal of the mission is to demonstrate the value of near-real-time GPS RO observation in operational numerical weather prediction. With the ability of performing both rising and setting occultation, the mission provides about 1,600~2,400 atmospheric and ionospheric soundings per day in near real-time that give vertical profiles of temperature, pressure, refractivity, and water vapor in neutral atmosphere, and electron density in the ionosphere with global coverage (Anthes et al, & 2008Liou et al, 2006aLiou et al, , 2006bLiou et al, , & 2007Fong et al, 2008aFong et al, & 2009a.…”
Section: Gnss Radio Occultation Missionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary scientific goal of the mission is to demonstrate the value of near-real-time GPS RO observation in operational numerical weather prediction. With the ability of performing both rising and setting occultation, the mission provides about 1,600~2,400 atmospheric and ionospheric soundings per day in near real-time that give vertical profiles of temperature, pressure, refractivity, and water vapor in neutral atmosphere, and electron density in the ionosphere with global coverage (Anthes et al, & 2008Liou et al, 2006aLiou et al, , 2006bLiou et al, , & 2007Fong et al, 2008aFong et al, & 2009a.…”
Section: Gnss Radio Occultation Missionmentioning
confidence: 99%
“…The mission results have shown that the RO data from FORMOSAT-3 are of better quality than those from previous missions and penetrate much further down into the troposphere, mission results could be referred to Liou et al (2007), Anthes et al (2008), Fong et al (2008a, 2008c& 2009a), and Huang et al (2009. In the near future, other GNSS, such as the Russian Global Navigation Satellite System (GLONASS), and the planned European Galileo system, could be used to extend the applications by the use of RO technique Fong et al, 2009aFong et al, & 2009b.…”
Section: Gnss Radio Occultation Missionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dash lines are the planned sched ule and the dots recorded the ex e cu tion re sults of the thrust ing. The FM3 encoun tered the so lar ar ray drive mech a nism anom aly and this blocks the FM3 thrust burn ac tiv ity to be de ployed at the 800 km mis sion or bit af ter reach ing the 711 km orbit (Fong et al 2008a). …”
Section: Fi Nal Con Stel La Tion and Ex Tended Mis Sion Phasementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Moreover, an increasing number of planned small spacecraft missions are in need of propulsive capability. Propulsion devices supply the spacecraft with attitude control, station keeping, and orbit transfer.…”
Section: Introductionmentioning
confidence: 99%